Ramifications of the ICC Arrest Warrant in Resolving the Israel-Palestine Conflict - Ramisa Jahan (APPTHI, 2024)
The situation in Palestine was referred to the International Criminal Court (ICC) in 2015. This study highlights the various hurdles that remain ahead of the Court and argues that the key essence of international law is to ensure the harmonious coexistence of nations, while at the same time respecting states' sovereignty. The study employed a qualitative research and normative legal approach, relying on primary and secondary sources of international law. The study reveals that following the establishment of the Court's jurisdiction and upon conducting a thorough investigation, the Court affirmed the commission of war crimes by Israel, which fall within the ambit of the Rome Statute, thus allowing the Court to prosecute the war criminals. Consequently, in 2024, the Office of the Prosecutor (OTP) issued arrest warrants against Israeli and Hamas leaders. Despite the ICC having the mandate to try individuals for the alleged commission of international crimes, the enforcement of such arrests has often been a matter of speculation, since the ICC is encircled with numerous stumbling blocks in effectuating the arrests. The Court uses arrest warrants to pressure states to prosecute perpetrators domestically and avoid armed conflicts, as shown by urgent mediation and ceasefire proposals after the OTP announcement.